Developing a quality improvement project to tackle the desflurane problem - King Sin Ang; Zhao Kai Low; Bryan Su Wei Ng; Pei Kee Poh (BMJ Open Quality)
Anaesthesia is associated with the routine use of volatile anaesthetic agents, all of which are potent greenhouse gases in varying degrees. Desflurane, in particular, has a high global warming potential and in recent years, there has been a global movement to reduce or remove its usage entirely from operating theatres. We work in a large tertiary teaching hospital in Singapore with deeply entrenched practices of using desflurane to facilitate high turnover of operating theatre cases. We launched a quality improvement project to (1) reduce the median usage of desflurane by 50% (by volume), and (2) reduce the number of theatre cases administering desflurane by 50% over a period of 6 months.We collected baseline data to determine departmental monthly median usage of desflurane. We then deployed sequential quality improvement methods to educate staff and to eliminate misconceptions, as well as to promote a gradual cultural change.We successfully reduced monthly median desflurane usage from 31.5 L to 12.2 L per month (61.3% reduction) within our targeted time frame. We also achieved a reduction in the number of theatre cases using desflurane by approximately 80%. This translated to significant cost savings of US$195 000 per year and over 840 tonnes of carbon dioxide equivalents saved.Healthcare is a resource intensive industry. Anaesthetists are well placed to play an important role in reducing healthcare-related carbon emissions by choosing anaesthetic techniques and resources responsibly. Through multiple Plan-Do-Study-Act cycles and a persistent, multifaceted campaign, we achieved a sustained change in our institution.